2022
DOI: 10.3390/ijerph19169825
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tongue Pressure and Jaw-Opening Force in Older Adults

Abstract: Tongue pressure (TP) is used to assess tongue muscle strength and is related to function and frailty. While performing TP, it is necessary to elevate the tongue and oral floor by contracting the suprahyoid muscles. However, the association between TP and suprahyoid muscle strength remains unclear. Accordingly, this study investigated the relationship between TP and jaw-opening force (JOF), an indicator of suprahyoid muscle strength. This cross-sectional study included 88 independent community-dwelling particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This strongly suggests that activation of the S‐hyo muscles contributed to exertion of the maximum effort of LP generation. This contention is also supported by one investigational study of community‐dwelling older adults, in which a positive correlation between the maximum LP value and the cross‐sectional muscle area of the geniohyoid muscle, rather than that of the I‐ton muscles was found 18 …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This strongly suggests that activation of the S‐hyo muscles contributed to exertion of the maximum effort of LP generation. This contention is also supported by one investigational study of community‐dwelling older adults, in which a positive correlation between the maximum LP value and the cross‐sectional muscle area of the geniohyoid muscle, rather than that of the I‐ton muscles was found 18 …”
Section: Discussionmentioning
confidence: 65%
“…This contention is also supported by one investigational study of community-dwelling older adults, in which a positive correlation between the maximum LP value and the cross-sectional muscle area of the geniohyoid muscle, rather than that of the I-ton muscles was found. 18 The MPF of the EMG burst of the S-hyo muscles in the early stage differed significantly among the four strength conditions; the stronger the LP was, the larger the MPF. This may be because differences in the number of activated muscle fibres depend on the LP strength.…”
Section: Discussionmentioning
confidence: 93%
“…The subjects were Eichner A patients and systemically healthy, and the hypotheses were that there were limited differences between males and females. As described, the values of these oral functions were associated with perioral muscle strength [8,[27][28][29]. The previous study showed that some oral functions in males were significantly higher than those in females [17].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding MOF and MTP, both functions were closely associated with some perioral muscles [8,[27][28][29]. The development of these muscles in childhood, and sex differences are also associated with MOF and MTP in these generations [17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers consider that the loss of muscle strength and occlusal function caused by tooth loss contributes to decreased tongue force [8,35]. Nonetheless, these studies found no positive or negative association between tongue pressure and the number of remaining teeth, which was expected to strengthen tongue pressure as compensation for tooth loss in order to maintain masticatory function [37]. Achieving optimal occlusal stability is crucial for ensuring safe swallowing [31].…”
Section: Discussionmentioning
confidence: 99%